SEDIMENT TRANSPORT BEHAVIOUR IN A STRAIT UNDER THE INFLUENCE OF CURRENTS - Mahendra Andiek Maulana; A.A. Ngr. Satria Damarnegara (Journal of Marine-Earth Science and Technology, 2025)
The Madura Strait, one of the most congested shipping lanes in Indonesia has been an important shipping route since the 13th century until recent days. The problem that exists in Madura strait is excessive sediment supply from river. This condition has disrupted several infrastructure facilities in the Madura Strait as happened at the Petrokimia Gresik port that is experiencing massive sedimentation. As one of the main supporting facilities in the factory, the existence and continuity of the port is important to always be maintained. This is related to the shallowing that often occurs in turning basin area. To estimate the shallowing process due to sedimentation in the pier pool, an analysis using a numerical model approach was applied. Based on the analysis, the current velocity in the turning basin area ranged from 0.10 to 0.20 m/s. In some conditions, the current velocity tends to approach 0 m/s which indicates a sedimentation zone was formed. Further, the analysis of bottom sediment movement shows the density of sediment material around the turning basin area ranged between 0.03 and 0.06 kg/m3. This condition leads seabed shallowing by 5.5 cm/month threatens navigability.